Ectomycorrhizal inoculation with Astraeus odoratus accelerates establishment, functional growth traits, and survival of Dipterocarpus turbinatus in degraded tropical forests - Vannasinh Souvannasouk; Odeth Sihavong; Phoukhanh Sayavongsa; Phoutsavath Phanthavong; Sisamone Xaiyakanya; Daochay Xayyavong (Maejo International Journal of Energy and Environmental Communication, 2025)
Successful restoration of degraded tropical forests requires high-quality seedlings that can establish fast and are environmentally resilient. Dipterocarpus alatus (Gurjan) is a timber species of construction and furniture and most of the seedlings do not survive after transplanting, making the reforestation less effective. This study examined the effect of Astraeus odoratus, an edible ectomycorrhizal fungus, on seedling growth and nutrient uptake in the field. Four-month-old nursery-grown seedlings were inoculated with a liquid suspension of basidiospores (50 mL seedling-1), and non-inoculated seedlings were used as controls. Growth parameters, accumulation of biomass, root colonization, and soil nutrient status were measured after four months, followed by the monitoring of the field transplant. Inoculated seedlings had much greater height (37.8 cm) and root collar diameter (5.89 mm) than controls (26.4 cm and 3.75 mm, respectively). Total dry biomass was also higher in treated seedlings (3.01 g) than in non-inoculated plants (2.34 g). According to the results, microscopic observations revealed ectomycorrhizal colonization with lateral roots and fungal sheaths. Enhanced phosphorus mobilization was through fungal enzymes. Inoculated seedlings had superior growth, a sign of successful establishment. Results confirm that A. odoratus bioaugmentation improved the growth of D. alatus. Integrating edible ectomycorrhizal fungi in nurseries offers a sustainable approach for restoring tropical forestry in the context of advantages for communities.